Multi-objective spatial optimization to balance trade-offs between farmland bird diversity and potential agricultural net returns - Maximilian Wesemeyer; Johannes Kamp; Tillman Schmitz; Daniel Müller; Tobia Lakes (Agriculture, Ecosystems & Environment, 2023)
Global farmland biodiversity has declined rapidly in recent decades due to the homogenization of agricultural landscapes, including an increase in field sizes and decrease in woody features, such as hedgerows. Restructuring landscapes by (re)introducing woody features and decreasing field sizes can support biodiversity but at the cost of lower returns in farming. Striking a balance between biodiversity and agricultural net returns is increasingly pertinent. Here, we use spatial multi-objective optimization to allocate woody features and adapt average field sizes at the landscape scale to assess the trade-off between biodiversity, measured as the occurrence of farmland birds, and potential net returns from crop production. Our results suggest that, compared to the current landscape configuration, both agricultural net returns and biodiversity can be simultaneously increased. Restructuring only 5% of the landscape can improve bird abundance by 2% and generate about exteuro2 million in agricultural net returns. We show that increases in farmland bird diversity are highly dependent on the location and on farmers' willingness to accept negative impacts on agricultural net returns. Our spatially explicit approach supports spatially targeted land use planning that can strike a better balance between the economic objectives of farmers and the societal desire to conserve biodiversity.
Keywords: 630; linear programming; field size; hedgerows; win-win solutions; trade-offs